STRATEGI MEMBANGUN BRAND ENGAGEMENT IKLAN SIRUP MARJAN PADA FESTIVE SEASON - Suryani, Ita; Marta, Rustono Farady; Chinmi, Maichel (LPPM-PMP Universitas Tidar, 2023)
PT Lasallefood Indonesia is a beverage-producing company, namely Marjan. This Ramadan moment was taken advantage of by Marjan Syrup to issue a new advertisement, released and premiered on February 25, 2023, on television. Carrying the theme